Effects of Gd addition on the thermal and microstructural behaviors of the as-cast Cu-9 % Al and Cu-9 % Al-10 % Mn alloys - Brazolin, G. F.; Canbay, C. Aksu; Ozgen, S.; Oliveira, A. B.; Silva, R. A. G. (Springer, 2016)
The effects of Gd addition on the thermal and microstructural behaviors of as-cast samples of the Cu-9 % Al and Cu-9 % Al-10 % Mn alloys were investigated using different experimental techniques. The results showed that the addition of Gd does not significantly interfere in the melting and solidification temperatures of the Cu-9 % Al alloy, but it decreases the stability of beta' martensitic phase during re-heating of sample, while the presence of Mn slows the beta(A2) phase decomposition during cooling and widens its stability field. The Cu-9 % Al-10 % Mn-3 % Gd alloy has characteristics close to those observed for the Cu-9 % Al-10 % Mn alloy, but the presence of Mn increases the solubility of Gd and induces the formation of Gd-rich precipitates with average size of 200 nm.
Keywords: Shape-Memory Alloys; Phase-Stability; System